2002
DOI: 10.1303/aez.2002.43
|View full text |Cite
|
Sign up to set email alerts
|

Artificial rearing of Nezara viridula(L.) and N. antennata Scott(Heteroptera: Pentatomidae) with semi-solid meridic diets.

Abstract: Semi-solid meridic diets for rearing two related species of Pentatomidae, Nezara viridula and N. antennata, were developed. For N. viridula, development times from second nymphal stadium to adult were 27.6 to 28.2 d for females and 26.8 to 27.5 d for males reared on the meridic diets at 25°C. The nymphal survival rate of N. viridula on the diets was more than 87%. Body weight at adult emergence ranged from 157.6 to 160.1 mg for females and from 123.1 to 128.3 mg for males. The pre-oviposition period was 20.8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
2
10
0
3
Order By: Relevance
“…An elongation of the 2 nd instar-adult period for both species was observed when 26.9 ± 0.14 a 5.6 ± 0.05 a 5.1 ± 0.51 a 6.3 ± 0.12 a 9.9 ± 0.13 a E. heros C 25.7 ± 0.28 b 5.3 ± 0.03 b 4.9 ± 0.06 ab 5.9 ± 0.13 a 9.6 ± 0.15 a nymphs were reared on all three artificial diets (Table 2). This has also been observed previously for other heteropterans reared on different artificial diets (Jensen & Gibbens 1973, Panizzi et al 2000, Noda & Kamano 2002, and was shown to correlate with the inadequate nutritional quality of the diet (Panizzi & Rossini 1987). Although the elongation in time observed was small (never > 1.6 days for both species) it still gives an indication of the nutritional unsuitability of the tested diets (Panizzi 1991, Parra 1991.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…An elongation of the 2 nd instar-adult period for both species was observed when 26.9 ± 0.14 a 5.6 ± 0.05 a 5.1 ± 0.51 a 6.3 ± 0.12 a 9.9 ± 0.13 a E. heros C 25.7 ± 0.28 b 5.3 ± 0.03 b 4.9 ± 0.06 ab 5.9 ± 0.13 a 9.6 ± 0.15 a nymphs were reared on all three artificial diets (Table 2). This has also been observed previously for other heteropterans reared on different artificial diets (Jensen & Gibbens 1973, Panizzi et al 2000, Noda & Kamano 2002, and was shown to correlate with the inadequate nutritional quality of the diet (Panizzi & Rossini 1987). Although the elongation in time observed was small (never > 1.6 days for both species) it still gives an indication of the nutritional unsuitability of the tested diets (Panizzi 1991, Parra 1991.…”
Section: Resultssupporting
confidence: 82%
“…This value was similar to that reported by Panizzi et al (2000) using a similar diet, but with different ingredients proportion. Noda & Kamano (2002) obtained a reduction in the time of nymph development when N. viridula was reared on an artificial diet containing casein, starch, dextrin, sucrose, soybean oil, and cellulose; this diet is similar to the one used to rear the alydid R. clavatus (Noda & Kamano 1983).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the occurrence of nonovipositing females may be attributed to the nutrition contents of E. kuehniella eggs as a diet. For example, Noda and Kamano (2000) reported that southern green stink bug, Nezara viridula (L.), females fed on artificial diets laid as many eggs as females fed on plant seeds, whereas some females failed to lay any eggs. They also suggested that some nutrition contents in the diet might affect the fecundity of the bug.…”
Section: Discussionmentioning
confidence: 99%
“…Noda e Kamano (2002), adequaram esta dieta de R. clavatus para uma dieta merídica semisólida, na criação de N. viridula e de N. antennata, adicionando dextrina e aumentando a quantidade de óleo de soja, observando, para a primeira espécie, uma viabilidade ninfal superior a 87% e fecundidade semelhante àquela das fêmeas alimentadas com sementes de soja e amendoim. Debolt (1982) foi o primeiro autor a publicar resultados promissores na utilização de dietas artificiais para heterópteros, utilizando uma dieta merídica líquida em vidros selados com "parafilm".…”
Section: Dieta Artificial Na Criação De Pentatomídeos Fitófagosunclassified